Cytotoxicity and inhibition of nitric oxide in lipopolysaccharide induced mammalian cell lines by aqueous extracts of brown seaweed - Jaswir, Irwandi; Monsur, Hammed Ademola; Simsek, Senay; Amid, Azura; Alam, Md Zahangir; Salleh, Mohammad Noor; Tawakalit, Asiyanbi-Hammed; Octavianti, Fitri (Japan Oil Chemists' Society, 2014)
Aqueous extracts obtained from five Malaysian brown seaweeds; Sargassum duplicatum, Sargassum binderi, Sargassum fulvellum, Padina australis and Turbinaria turbinata, were investigated for their abilities to inhibit Nitric oxide (NO) production in lipopolysaccharide (LPS) induced macrophage RAW 264.7 cell lines as well as their chemical composition. Percentage yield of extracts varied among species, with the least yield in P. australis and highest yield in T. turbinata. The chemical compositions of the extracts showed that percentage sulfate ion, uronic acid and total sugar contents vary remarkably. All extracts contain high fucose and inhibit NO secretion in a dose dependent manner. Percentage of NO inhibition correlates very well with uronic acid content of the extract. Extracts of P. australis and T. turbinata dosed as 200 g/ml where able to cause >75% NO inhibition. Cytotoxicity assay revealed that some extracts were moderately toxic while some are not. Brown seaweed of Malaysian origin can be further explored for additional anti-inflammatory biocompounds.